The Brazilian cohort of pulp and paper workers: the logistic of a cancer mortality study Coorte brasileira de trabalhadores de indústria de celulose e papel: a logística de um estudo de mortalidade por câncer - Anaclaudia Gastal Fassa; Luiz Augusto Facchini; Marinel Mór Dall'Agnol (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1998)
The International Agency for Research on Cancer (IARC) proposed this international historical cohort study trying to solve the controversy about the increased risk of cancer in the workers of the Pulp and Paper Industry. One of the most important aspects presented by this study in Brazil was the strategies used to overcome the methodological challenges, such as: data access, data accuracy, data availability, multiple data sources, and the large follow-up period. Through multiple strategies it was possible to build a Brazilian cohort of 3,622 workers, to follow them with a 93 percent success rate and to identify in 99 percent of the cases the cause of death. This paper, has evaluated the data access, data accuracy and the effectiveness of the strategies used and the different sources of data. A Agência Internacional para Pesquisa sobre Câncer (IARC) propôs uma coorte histórica internacional para tentar resolver a controvérsia sobre o risco aumentado de câncer em trabalhadores das indústrias de celulose e papel. Um dos aspectos mais relevantes deste estudo no Brasil refere-se às estratégias utilizadas para superar desafios metodológicos, tais como: acesso aos dados, acurácia e disponibilidade dos dados, múltiplas fontes de dados e longo período de acompanhamento. Através de múltiplas estratégias, foi possível construir uma coorte brasileira de 3.622 trabalhadores, acompanhar 93% dos casos e identificar a causa de 99% dos óbitos. Este artigo avalia o acesso aos dados, sua acurácia e a efetividade das estratégias utilizadas para o acompanhamento da coorte.